'Behind every stone awaits an Alexander': unravelling the limits of participation within micro and macro dramaturgy of participatory refugee theatre. Issue 2 (3rd April 2018) - de Smet, Sofie; De Haene, Lucia; Rousseau, Cécile; Stalpaert, Christel
ABSTRACT: In this article, we question the unilateral discourse of benefit of participation in participatory refugee theatre in the context of a growing socio-political climate of polarisation and stigmatisation of refugees in European countries of resettlement. By integrating critical voices from the fields of applied theatre and refugee research, we analyse the micro and macro dramaturgy of a Berlin-based participatory refugee theatre project. Through this analysis, we explore how refugees' participation entails opportunities for empowerment, agency and giving voice, but also risks disempowerment and silencing in the interconnected relations between the participant, theatre maker, audience and the broader socio-political context.